How to evaluate political education programs? A methodological debate (Simbiótica. Revista Eletrônica, 2026)
Universities are breeding grounds for political education outreach projects; some are long-standing, making these institutions benchmarks in the field, while initiatives in this area are carried out by a myriad of actors. This article aims to discuss methodological approaches to applied research for evaluation, considering the theoretical debate on political education actions, since in a large part of these initiatives, one of the greatest challenges lies in evaluation, whether as a way to improve their activities or as a need for transparency within the institutional spaces where they are developed.  Based on a review of the literature and practical evaluation experiences, this article helps to revitalize the debate on the effects of political education actions, programs, and projects on the public from the perspective of those who promote them. The main contribution is the construction of a synthesis of fundamental evaluative elements in political education actions.
Keywords: assessment; university outreach; political socialization; education for democracy